Cultivation of In-vitro-Fertilization according the Details of One of the Four Islamic Doctrines (Islamic Sciences Journal, 2024)
Islamic jurisprudence integrates both traditional and contemporary elements, ensuring that every situation is subject to a legal ruling. Prior to issuing a ruling, a thorough understanding of the matter at hand is necessary, ensuring that the decision is informed by medical expertise. Artificial insemination refers to any non-traditional method of fertilization involving the introduction of sperm from a male into the reproductive system of a female for the purpose of fertilizing an egg. The jurists have had varying opinions on this matter. However, legal regulations have been established to ensure the confidentiality of the surgery and the ongoing existence of indicators.
Keywords: artificial insemination, tubes, Hanafis, jurists.